Effect of DOPA and dopamine coupling on protein loading of hydroxyapatite - Kollath, V. Ozhukil [UNESP]; Mullens, S.; Luyten, J.; Traina, K.; Cloots, R. (Taylor & Francis Ltd, 2016)
Hydroxyapatite (HA) is a promising carrier material for oral delivery of biomolecules such as proteins and drugs. Ways to increase the loading of such molecules on HA will lead to better nanomedicine. This study reports the surface functionalisation of HA particles using the mussel inspired molecules dopamine (DA) and 3,4-dihydroxy-L-phenylalanine (DOPA), in order to increase protein loading. The adsorption mechanisms are discussed based on the adsorption isotherms, zeta potential, thermal analysis and theoretical models. Results show that DA functionalisation enhanced the loading, while DOPA functionalisation was ineffective.
Keywords: Hydroxyapatite; Protein; Dopamine; Adsorption isotherm; Oral delivery